Pengaruh Aktivitas Pasar dan Reputasi Underwriter terhadap Excess Returns Saham IPO di Bursa Efek Indonesia - Utamaningsih, Arni (Jurnal Kajian Manajemen Bisnis, 2014)
This study provides comprehensive analysis of an IPO (Initial Public Offering) underwriting process.  It  considers  the  set  of  actions  that  an underwriter  undertakes  as  an  integrated process, explicitly recognizing the interdependencies among pre market, issue-date, and aftermarket underwriter activities. It can be drawn only if these relationships are fully rather than partially considered. This analysis clarifies the relationships between the various underwriter activities and the returns that investors earn during different periods after the offerings. It also shows that an underwriter reputation has implications for both underwriter activities during the underwriting process and investor returns.Underwriter  reputation  is  a  positive  but  weakly  determinant  of  pre  market underwriter  activities,  unrelated  to  aftermarket  price  stabilization  activities,  and unrelated  to  investor  returns.  Pre  market  underwriter  activities  are  a  significant determinant  of  initial  returns  but  unrelated  to  aftermarket  activities  and  short-run returns. Initial returns are significantly related to aftermarket underwriter activities and longer-run returns. The results suggest for a simultaneous consideration of underwriter reputation and market activities, and for which path analysis can be drawn about the IPO as a set of process and investor returns.